The Impact of Financial Markets to the Finance of the Country - Jo’rayev Og’abek (European Science Publishing, 2023)
The financial market mobilizes free funds and turns them into financial resources, idle money in the hands of the population into a source of income. The financial market, which includes deposits, bills, foreign exchange, stock, bond, derivative and insurance markets, is usually the driving force of the economy. It serves to solve social problems by developing the financial market, improving the competitive environment, promoting the use of new types of financial management, attracting investments to business entities, and creating additional jobs.
Keywords: financial market, stock market, transnational corporations, international financial relations.